A transitional desmosome/tonofibril network may relay mechanical strain to epidermal nerve terminals with high fidelity and sensitivity in the Cuban crocodile (Crocodylus rhombifer): an ultrastructural study - Melkersson, Karl-Gunnar; Hodik, Monika; Staxäng, Karin; Hakizimana, Pierre; Li, Hao; Rask-Andersen, Helge (Frontiers in Cell and Developmental Biology, 2026)
BackgroundCrocodilians are well endowed with multiple cutaneous receptors and specializations, such as integumentary sensory organs (ISOs), which provide formidable mechanical sensitivity despite their protected shield. We investigated the free intraepidermal nerve terminals, focusing on the desmosomes, transitional desmosomes (TDs), corneodesmosomes (CD), and the tonofibril (TF) network that potentially act as force transducers to activate the mechanoreceptors.Material and MethodsTwo Cuban crocodiles (Crocodylus rhombifer) were analyzed using light and transmission electron microscopy (TEM) after glutaraldehyde fixation and decalcification.ResultsDiscoid nerve terminals were richly enclosed by an epidermal force-transmitting system (e.g., pressure and vibration) through a rigid network of diverse desmosomes and CDs. TDs were anchored to keratinocyte’s cytoskeletons via a dense meshwork of intermediate filaments or TFs, creating a continuous, mechanically-linked web connecting nerve terminals in the epidermis to the stratum corneum. The cutaneous receptors were innervated by myelinated and unmyelinated neural complexes surrounded by thin-walled mesothelial cells.DiscussionHere, we describe for the first time the ultrastructure of TDs in the crocodile skin with diverse expression of CDs that may focus and amplify force via a tonofibril system “hugging” the receptor. Corneocytes, granular keratinocytes, and nerve endings function as a single integrated system. Thereby, mechanical strain is gathered from a relatively large area of the epidermis and concentrated onto the small surface of the discoid receptor. This may ensure that any deformation of the surrounding corneocytes is efficiently and reliably transferred to the nerve membrane, allowing the crocodile to detect very subtle stimuli. The crocodile system appears to have a far more structured and specialized adaptation for high-fidelity mechanosensation than that of humans.